Maternal organokines throughout pregnancy as predictors of neonatal anthropometric characteristics and adiposity - Valencia-Ortega, Jorge; Galicia-Hernández, Victoria; Castillo-Santos, Andrea; Molerés-Orduña, Miranda; Arceo-Cerna, Carla; Perichart-Perera, Otilia; Rodríguez-Cano, Ameyalli M.; Rodríguez-Hernández, Carolina; Estrada-Gutierrez, Guadalupe; Camacho-Arroyo, Ignacio; Solis-Paredes, Juan Mario (Frontiers in Endocrinology, 2024)
To evaluate the relation between maternal concentrations of progranulin (PGRN), adipocyte fatty acid-binding protein (AFABP), brain-derived neurotrophic factor (BDNF), and fibroblast growth factor 21 (FGF21) throughout pregnancy with neonatal weight and length at birth and at one month of age, as well as with the percentage of fat mass at one month of age. Besides, we evaluated the association between maternal organokine concentrations with pregestational nutritional status and gestational weight gain (GWG).Methods: Longitudinal study of 100 healthy pregnant women and their neonates. Conventional biochemical tests were performed and maternal organokine concentrations were measured by ELISA. Neonatal percent fat mass was determined using the PEA POD system, and weight and length were measured using a soft tape measure and a baby scale. Multiple linear regression models were made to predict neonatal anthropometric measurements and adiposity.Results: In all women, PGRN concentrations significantly increased as pregnancy progressed, while AFABP concentrations increased until the third trimester and the highest BDNF concentrations were observed in the second trimester of pregnancy. In contrast, FGF21 concentrations did not change during pregnancy. Only maternal obesity was associated with some differences in AFABP and FGF21 concentrations. Gestational age at birth, maternal age and third-trimester PGRN concentrations predicted weight (gestational age at birth: β=0.11; maternal age: β=-0.033; PGRN: β=0.003, p˂0.001) and, together with first-trimester BDNF concentrations, length (gestational age at birth: β=0.76; maternal age: β=-0.21; PGRN: β=0.24; BDNF: β=0.06, p˂0.001) at birth. Maternal age and third-trimester BDNF concentrations predicted one-month-old neonate length (maternal age: β=-1.03; BDNF: β=0.45, p˂0.001). Pregestational body mass index (pBMI), GWG, second-trimester FGF21 concentrations, and third-trimester AFABP concentrations predicted neonatal fat mass percentage (pBMI: β=-0.58; GWG: β=-0.32; FGF21: β=-0.004; AFABP: β=-1.27, p˂0.001) at one month of age.Maternal PGRN, AFABP, and BDNF concentrations, but not FGF21, vary throughout pregnancy. These organokines and maternal characteristics can be useful in the prediction of neonatal weight, length, and percentage fat mass.